(untitled) (Journal of Partial Differential Equations, 2008)
" In this paper, some properties of three-dimensional Stokes equations with boundary condition of pressure on parts of boundary are studied. By use of these properties, approximate controllability by tangent boundary controls acting on a subboundary is studied. In addition, the controllability problem is considered when its controls act on a subdomain."